SUN-LB42 The Sexually Dimorphic Response of the Mouse Adrenal Inner Cortex to Thyroid Hormone Treatment - Zheng, Huifei Sophia (J Endocr Soc, 2020)
The gender bias in adrenal diseases has been noticed for a long time. Mouse studies have shown that the adrenal gland is sexually dimorphic at different levels, such as transcriptome, histology, and cell renewal. However, the mechanism behind this sexual dimorphism is not fully understood. Here, we used RNA-seq to demonstrate how male and female adrenals respond differently to the same external cue, the thyroid hormone (T3) treatment, which directly elicits its function on the adrenal inner cortex by changing the cell fate of this population. Through the comparison of the adrenal gland transcriptomes from males and females with T3 or saline treatment, we found that more genes in female adrenals were responsive to the T3 treatment, whereas the fold change of the gene expressions was greater in male adrenals. Statistical analysis identified 104 sexually dimorphic T3-responsive genes. Immunostaining results showed that many of these genes were expressed in the adrenal gland inner cortex, which contains a unique cell population called X-zone (20-alpha-HSD positive). Previous studies showed that T3 treatment leads to the expansion of the 20αHSD-positive zone both in males and in females. Here we found that the top sexually dimorphic T3-responsive gene was expressed in the adrenal inner cortex partially colocalized with X-zone. Under T3 treatment, this unique cell population that surrounds the 20-alpha-HSD positive X-zone became obvious only in females but not in males. Our findings not only identified several novel marker genes for the adrenal inner cortex but also highlighted the sex-specific response of thyroid hormone action in the mouse adrenal gland.